Proceedings of First International Electronic Conference on the Hydrological Cycle 2017
DOI: 10.3390/chycle-2017-04877
|View full text |Cite
|
Sign up to set email alerts
|

<strong>Patterns of atmospheric moisture transport linked to Southern Ocean Sea ice coverage changes</strong>

Abstract: and Amundsen and Bellingshausen seas. For most of these seas it was identified positive trends of E-P>0 anomalies, while negative trends were identified only for the SAUS moisture source to Amundsen and Bellingshausen Sea. In terms of SIC, for the whole Antarctic the total anomalies are increasing, but no breaking points in this time serie were detected. Preliminary results also indicate some areas, which do not coincide exactly with the limit of the regional seas, where the increase of Sea Ice Extension (SIE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…By using observational and reanalysis data alone it is difficult to disentangle which of the potential drivers (e.g., IWV and T2m) has a stronger impact on the sea ice variability. For the Arctic region, previous studies (Mortin et al, 2016;Kapsch et al, 2013;Park et al, 2015) suggested that the transport of heat and moisture into the Arctic during spring enhances the incoming surface longwave radiation, thereby controlling the initiation of the annual ice melt and setting the stage for the Arctic September ice minimum. Thus, our study can be used as an indicator that moisture transport should be considered in future studies as a potential driver of the Antarctic sea ice variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By using observational and reanalysis data alone it is difficult to disentangle which of the potential drivers (e.g., IWV and T2m) has a stronger impact on the sea ice variability. For the Arctic region, previous studies (Mortin et al, 2016;Kapsch et al, 2013;Park et al, 2015) suggested that the transport of heat and moisture into the Arctic during spring enhances the incoming surface longwave radiation, thereby controlling the initiation of the annual ice melt and setting the stage for the Arctic September ice minimum. Thus, our study can be used as an indicator that moisture transport should be considered in future studies as a potential driver of the Antarctic sea ice variability.…”
Section: Discussionmentioning
confidence: 99%
“…Turner et al (2017) considered the spatial differences of the SIE anomalies and their temporal change at a regional level. They related the low SIE over the Antarctic region to the warm air advection and the strong negative values of the SAM in November andDecember 2016. Schlosser et al (2018) have shown that the rapid decrease in the sea ice area and extent were associated with atmospheric flow patterns reminiscent of a positive ZW3 index.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation